Breast cancer screening in Lebanon: Understanding knowledge, attitudes and barriers - Tamina Elias-Rizk; Elio Issa; Emmanuel Ammanouil; Melissa Abou Khalil; Pascale Salameh; Aniella Abi-Gerges (Elsevier, 2024)
Background: Breast cancer (BC) has been increasing in both prevalence and incidence in Lebanon. Knowing the positive impact mammographic screening has on reducing mortality rates, we sought to investigate the knowledge, attitudes and barriers towards BC screening amongst Lebanese women across all districts. Methods: We conducted a cross-sectional study with 400 Lebanese women aged 35-75, with no prior or current diagnosis of BC, employing an online questionnaire filled face-to-face with participants to gather sociodemographic data and assess BC history and screening practices. We utilized the Breast Cancer Screening Beliefs Questionnaire (BCSBQ) and Champion Health Belief Model Scale (CHBMS) to evaluate knowledge, attitudes, and barriers. Results: Findings revealed inadequate attitudes towards general health check-ups (77.5 %) and insufficient BC screening knowledge (56.4 %). Furthermore, 38.5 % encountered obstacles to mammography screening. Education significantly affected BC knowledge. Interestingly, increased knowledge of BC reduced barriers to mammographic screening. Participants with healthcare connections or background exhibited better attitudes towards health check-ups and encountered fewer screening obstacles. Conclusion: This is the first study that endeavors to comprehensively investigate Lebanese women's knowledge, attitudes, and barriers concerning BC screening, encompassing all demographics and regions using validated scales (BCSBQ and CHBMS). Our data highlight the crucial role of education in advocating for early BC screening and the necessity to reevaluate national campaigns, particularly in communication methods, to ensure equitable access to screening across Lebanon.